Defining Spasticity: A New Approach Considering Current Movement Disorders Terminology and Botulinum Toxin Therapy - Chana-Cuevas, P (Dr. Dietrich Steinkopff Verlag GmbH and Co. KG, 2018)
Spasticity is a symptom occurring in many neurological conditions including stroke, multiple sclerosis, hypoxic brain damage, traumatic brain injury, tumours and heredodegenerative diseases. It affects large numbers of patients and may cause major disability. So far, spasticity has merely been described as part of the upper motor neurone syndrome or defined in a narrowed neurophysiological sense. This consensus organised by IAB—Interdisciplinary Working Group Movement Disorders wants to provide a brief and practical new definition of spasticity—for the first time—based on its various forms of muscle hyperactivity as described in the current movement disorders terminology. We propose the following new definition system: Spasticity describes involuntary muscle hyperactivity in the presence of central paresis. The involuntary muscle hyperactivity can consist of various forms of muscle hyperactivity: spasticity sensu strictu describes involuntary muscle hyperactivity triggered by rapid passive joint movements, rigidity involuntary muscle hyperactivity triggered by slow passive joint movements, dystonia spontaneous involuntary muscle hyperactivity and spasms complex involuntary movements usually triggered by sensory or acoustic stimuli. Spasticity can be described by a documentation system grouped along clinical picture (axis 1), aetiology (axis 2), localisation (axis 3) and additional central nervous system deficits (axis 4). Our new definition allows distinction of spasticity components accessible to BT therapy and those inaccessible. The documentation sheet presented provides essential information for planning of BT therapy. © 2018, Springer-Verlag GmbH Germany, part of Springer Nature.
Keywords: Spasticity; Rigidity; Dystonia; Spasms; Contractures; Treatment; Botulinum toxin therapy